The Origin Then and Now : An Interpretive Guide to the Origin of Species - Reznick, David N., 1952- (Book collections on Project MUSE., 2011)
Charles Darwin's Origin of Species is one of the most widely cited books in modern science. Yet tackling this classic can be daunting for students and general readers alike because of Darwin's Victorian prose and the complexity and scope of his ideas. The "Origin" Then and Now is a unique guide to Darwin's masterwork, making it accessible to a much wider audience by deconstructing and reorganizing the Origin in a way that allows for a clear explanation of its key concepts. The Origin is examined within the historical context in which it was written, and modern examples are used to reveal how t.